Dona Flor e seus dois maridos: traços de uma narrativa neopicaresca - Siqueira, Adriana Carolina de (2021)
This thesis analyzes the literary novel Dona Flor e Seus Dois Maridos (1968), written by Jorge Amado, in search for aspects that bring it closer or distance it from the neopicaresque aesthetic proposed by González (1994) in his book A Saga do Anti-Herói (1994), which was inspired by the picaresque narrative originally from Spain, in the 16th century, during the period of House Habsburg. The goal of this thesis is to relate the assumed adoption of the neopicaresque narrative style by Brazilian writer Jorge Amado with the literary expression strategy of the female eroticism being silenced in the fictional scenario of the city of Salvador in the 1940’s, considering that both the picaresque and the neopicaresque aesthetics have the purpose of giving voice to the marginalized part of society. The research developed herein is qualitative and based on survey and analysis of bibliographic data with the aim to reach answers. The analysis was made based on the study about the voice of the narrator and the design of the characters, drawing potential parallels between Amado’s novel, Dona Flor e Seus Dois Maridos, the picaresque novel Lazarilho de Tormes (1554), written by an Anonymous Author, and the neopicaresque novel Memórias de um Sargento de Milícias (1853), written by Manuel Antonio de Almeida, the latter being considered as the first Brazilian roguish literary novel. From the analysis of the 11 social situation of women in Brazil during the 19th and 20th centuries, and with historical basis provided for by the literary works Histórias Íntimas (2014), Histórias das Mulheres no Brasil (2017) and História do Amor no Brasil (2019), all written and organized by historian Mary del Priore, we enter the debate about the literary concepts of the picaresque, the roguish, and the neopicaresque in view of Candido’ theory in his essay Dialética da Malandragem (1970) and González (1994)’s theory in his books A Saga do Anti-Herói (1994) and O Romance Neopicaresco (1998). In another moment, we contemplate the novel Dona Flor e Seus Dois Maridos, analyzing its narrative focus, the design of its characters and their relationship with work and, also, the presence of eroticism in the narrative, relating it all to the neopicaresque aesthetic, a literary genre known by its criticism and complaints on social matters